Motivational Factors in Learning Foreign Languages: The Case of Russian - Pogadaev, V.A. (2007)
There are two types of motivation, that is, concrete motivation (instrumental) and universal motivation (Integral) when learning languages. The student with concrete motivation possess limited objectives such as to read books that are suitable or in accordance with their proficiency, listening to the radio, watching television programmes and others. Students with universal motivation will have more global objectives, such as, they will view learning foreign languages as a prerequisite or key for acquainting them with the country origin of the language. Both types of motivation will determine the extrinsic motivation. How is the situation for the Russian language in accordance to these views? For 288 million people the Russian language is the mother language or is a second language. Apart of this, according to UNESCO, 215 million people in the world use the Russian language as a foreign language. The Russian language is one of the job and official language of the United Nations. The desire to know about the the Russian culture is another motivation to learn the language. A number of foreigners are attracted to the beauty of the sound of the Russian language. Presently, The Russian language is widely used in business. But there are intrinsic motivation to wanting to learning the language which are related with the delivery process of learning a foreign language. The choice of books which are attractive, teaching methods which are encouraging, the creative organization and maintainance of language classes which could result in the desire to continue lrearning the language is important. In this article, the author uses the results from a survey conducted at the Faculty of Language and Linguistics, University of Malaya oin April 2006 to find out student’s interests in learning this language.